Moderating role of coping resources on relationships between factors and independent living readiness among incarcerated adolescents in Peninsular Malaysia - Tamil Chelvam, Thiresyinie (2022)
The process of incarceration among adolescents brings along potential implications before, during and after committing infringement acts. Despite that, numerous proceeding cases indicate that the problem remains as a stable threat at an alarming rate. Why is it that, even though sufficient guidance and support has been provided, repeated offences among these incarcerated adolescents are kept on increasing? The answer is unclear due to scare research conducted in this concern area. Yet, little is known about how well these incarcerated adolescents are equipped with relevant knowledge and skills to ensure their readiness for an independent living. Despite the findings of previous studies, it was not well established as to whether the self-esteem and alexithymia regulation would predict and reflect upon the readiness for independent living among incarcerated adolescents. Additionally, the role of coping resources towards the interrelationships between self-esteem and alexithymia regulation on the readiness for independent living is unclear. This study is therefore directed along with the above research gaps in mind, which is designed (1) to examine the relationship between self-esteem and alexithymia regulation on the readiness for independent living and (2) to determine the moderating effect of coping resources. In line with the study objectives, a two-stage cluster sampling method was used by this cross- sectional study in selecting the respondents from selected Sekolah Tunas Bakti in Peninsular Malaysia. A total of 255 questionnaires were distributed to incarcerated adolescents aged 12 to 18 years old. The findings revealed that the inclusion of the interaction term between self-esteem and readiness for an independent living with a coefficient β value of (β = .520, p ≤ 0.05), shows that coping resources works as a moderating variable in influencing the relationship. Interestingly, coping resources also acts as a moderating variable in influencing the relationship between alexithymia regulation and readiness for independent living among incarcerated adolescents; coefficient β value of (β = -.380, p ≤ 0.05). Contrary to what has often been assumed, this study brings out the novelty findings of a new dimension and empowers experience of studying the moderating role of coping resources which moderated the relationships of both self-esteem and alexithymia regulation on the readiness for independent living among incarcerated adolescents. Fundamental understanding on the readiness for independent living among incarcerated adolescents can be utilized as a source of output for the policy makers to provide supportive environment for these incarcerated adolescents especially in a Malaysia context. Therefore, interventions should be targeted on incarcerated adolescents' readiness to reintegrate with society and to live independently, namely, coping resources of his/her needs of support, information, and feedback to delineate the challenges lying ahead.